2021
DOI: 10.2991/assehr.k.210226.061
|View full text |Cite
|
Sign up to set email alerts
|

Error Analysis of Silent Letters and Its Relevance to the Teaching of English

Abstract: This research analyzes pronunciation errors of English words containing silent letters made by the first-year students of English Education Study Program at Tadulako University. The methodology used in this research is qualitative descriptive studies. The sample was selected by using purposive sampling techniques in which one class out of five parallel classes was chosen intentionally for research participants consisting of 37 students. Data were collected through test, in-depth interview, and questionnaire. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…Because of the variations in sound and orthography, learning English may be especially difficult for native Arabic speakers. Previous research has shown that interference from the native language in regions where it varies from the second or foreign language is a common source of spelling mistakes [10]. This research verifies the results of previous studies while also introducing a new factor: the type of classroom teaching and teacher education.…”
Section: Discussionsupporting
confidence: 88%
“…Because of the variations in sound and orthography, learning English may be especially difficult for native Arabic speakers. Previous research has shown that interference from the native language in regions where it varies from the second or foreign language is a common source of spelling mistakes [10]. This research verifies the results of previous studies while also introducing a new factor: the type of classroom teaching and teacher education.…”
Section: Discussionsupporting
confidence: 88%
“…There is no correlation between written and spoken words in English since English words are not usually spoken as they are written (Astuti et al, 2021). The similarity between words can be the cause of pronunciation errors.…”
Section: Words Similaritymentioning
confidence: 99%